Dose optimisation of 18F-flurodeoxyglucose for whole body PET oncology examination in CDNI of UPM - Hassan, Hishar; Mustafa, Salasiah; Ahmad Saad, Fathinul Fikri; Nordin, Abdul Jalil (Universiti Putra Malaysia Press, 2015)
A shift to administration of optimal dose of18F-FDG between 4 and 5 MBq/kg from the current practice of higher doses potentially yields a reasonable-to-excellent PET image. For this purpose, whole-body MIP images of 32 patients (23 men, 9 women, age 51.9 ± 13.7 years), administered with 18F-FDG (activity 5.3 ± 0.5 MBq/kg, 45 minutes uptake time) for whole-body PET/CT examinations, were evaluated. Image quality was assessed visually by two radiologists using a three-point scoring scale: poor, reasonable and excellent. The interobserver agreement revealed a kappa value higher than 0.7. Therefore, the utilisation of 18F-FDG dose between 4 and 5MBq/kg is considered an optimum dose for whole-body PET/CT examination.